Randomized cross-over trial of demand oxygen delivery system. Issue 19 (May 2020) - Nagano, Tatsuya; Kobayashi, Kazuyuki; Omori, Takashi; Otoshi, Takehiro; Umezawa, Kanoko; Katsurada, Naoko; Yamamoto, Masatsugu; Tachihara, Motoko; Nishimura, Yoshihiro
Abstract: Introduction: Long-term oxygen therapy is reported to improve hypoxemia and survival in patients with respiratory failure. The demand oxygen delivery system (DODS) saves oxygen and extends the usable time of an oxygen cylinder 2- to 3-fold. A portable oxygen concentrator with an auto-DODS has been developed to switch its sensitivity among 3 levels (standard, high, and extra high) and to supply pulsed-flow oxygen when it detects apnea. The aim of this study is to evaluate the efficacy of this newly developed portable oxygen concentrator with auto-DODS compared to the efficacy of conventional DODS in oxygenation. Methods and analysis: Twenty-six patients with chronic obstructive pulmonary disease or interstitial pneumonia will be randomized to use auto-DODS or conventional DODS at rest and during a 6-minute walk test. Primary endpoints are mean oxygen saturation (SpO2 ) at rest and during the 6-minute walk test. Secondary endpoints are the ratios of the times during which the oxygen concentrator operates at each sensitivity mode (standard, high, and extra high) and at a constant pulse rate to the examination time, the ratio of the times during which SpO2 fall below 90% to the examination time, the lowest value of SpO2 during the examination time, the mean and highest pulse rates during the examination time, 6-minute walking distance, recovery time, Borg scale, comfort, and reliability, which are measured by a numerical rating scale and a questionnaire, respectively. Ethics and dissemination: The study was conducted in accordance with the Declaration of Helsinki and was registered on Aug 23, 2019 (https://jrct.niph.go.jp/en-latest-detail/jRCTs052190041 ). The results of the study will be presented at academic conferences and submitted to a peer-reviewed journal. Trial registration number: jRCTs052190041